BioWatch and Public Health Surveillance: Evaluating Systems for the Early Detection of Biological Threats: Abbreviated Version - Institute of Medicine; National Research Council (The National Academies Press, 2011)
Following the attacks of September 11, 2001 and the anthrax letters, the ability to detect biological threats as quickly as possible became a top priority. In 2003 the Department of Homeland Security (DHS) introduced the BioWatch program2014a federal monitoring system intended to speed detection of specific biological agents that could be released in aerosolized form during a biological attack. The present volume evaluates the costs and merits of both the current BioWatch program and the plans for a new generation of BioWatch devices. BioWatch and Public Health Surveillance also examines infectious disease surveillance through hospitals and public health agencies in the United States, and considers whether BioWatch and traditional infectious disease surveillance are redundant or complementary.

Understanding and Managing Risk in Security Systems for the DOE Nuclear Weapons Complex: (Abbreviated Version) - National Research Council (The National Academies Press, 2011)
A nuclear weapon or a significant quantity of special nuclear material (SNM) would be of great value to a terrorist or other adversary. It might have particular value if acquired from a U.S. facility–in addition to acquiring a highly destructive tool, the adversary would demonstrate an inability of the United States to protect its nuclear assets. The United States expends considerable resources toward maintaining effective security at facilities that house its nuclear assets. However, particularly in a budget-constrained environment, it is essential that these assets are also secured efficiently, meaning at reasonable cost and imposing minimal burdens on the primary missions of the organizations that operate U.S. nuclear facilities. It is in this context that the U.S. Congress directed the National Nuclear Security Administration (NNSA)–a semi-autonomous agency in the U.S. Department of Energy (DOE) responsible for securing nuclear weapons and significant quantities of SNM–asked the National Academies for advice on augmenting its security approach, particularly on the applicability of quantitative and other risk-based approaches for securing its facilities. In carrying out its charge, the committee has focused on what actions NNSA could take to make its security approach more effective and efficient. The committee concluded that the solution to balancing cost, security, and operations at facilities in the nuclear weapons complex is not to assess security risks more quantitatively or more precisely. This is primarily because there is no comprehensive analytical basis for defining the attack strategies that a malicious, creative, and deliberate adversary might employ or the probabilities associated with them. However, using structured thinking processes and techniques to characterize security risk could improve NNSA's understanding of security vulnerabilities and guide more effective resource allocation.

Protecting the Frontline in Biodefense Research: The Special Immunizations Program - National Research Council (The National Academies Press, 2011)
The U.S. Army's Special Immunizations Program is an important component of an overall biosafety program for laboratory workers at risk of exposure to hazardous pathogens. The program provides immunizations to scientists, laboratory technicians and other support staff who work with certain hazardous pathogens and toxins. Although first established to serve military personnel, the program was expanded through a cost-sharing agreement in 2004 to include other government and civilian workers, reflecting the expansion in biodefense research in recent years. Protecting the Frontline in Biodefense Research examines issues related to the expansion of the Special Immunizations Program, considering the regulatory frameworks under which the vaccines are administered, how additional vaccines might be considered for inclusion in the Program, and factors that might influence the development and manufacturing of vaccines for the Special Immunizations Program.

Evaluation of U.S. Air Force Preacquisition Technology Development - National Research Council (The National Academies Press, 2011)
From the days of biplanes and open cockpits, the air forces of the United States have relied on the mastery of technology. From design to operation, a project can stretch to 20 years and more, with continuous increases in cost. Much of the delay and cost growth afflicting modern United States Air Force (USAF) programs is rooted in the incorporation of advanced technology into major systems acquisition. Leaders in the Air Force responsible for science and technology and acquisition are trying to determine the optimal way to utilize existing policies, processes, and resources to properly document and execute pre-program of record technology development efforts, including opportunities to facilitate the rapid acquisition of revolutionary capabilities and the more deliberate acquisition of evolutionary capabilities. Evaluation of U.S. Air Force Preacquisition Technology Development responds to this need with an examination of the current state of Air Force technology development and the environment in which technology is acquired. The book considers best practices from both government and industry to distill appropriate recommendations that can be implemented within the USAF.

Review of the Scientific Approaches Used During the FBI's Investigation of the 2001 Anthrax Letters - National Research Council (The National Academies Press, 2011)
Less than a month after the September 11, 2001 attacks, letters containing spores of anthrax bacteria (Bacillus anthracis, or B. anthracis) were sent through the U.S. mail. Between October 4 and November 20, 2001, 22 individuals developed anthrax; 5 of the cases were fatal. During its investigation of the anthrax mailings, the FBI worked with other federal agencies to coordinate and conduct scientific analyses of the anthrax letter spore powders, environmental samples, clinical samples, and samples collected from laboratories that might have been the source of the letter-associated spores. The agency relied on external experts, including some who had developed tests to differentiate among strains of B. anthracis. In 2008, seven years into the investigation, the FBI asked the National Research Council (NRC) of the National Academy of Sciences (NAS) to conduct an independent review of the scientific approaches used during the investigation of the 2001 B. anthracis mailings. Review of the Scientific Approaches Used During the FBI's Investigation of the Anthrax Letters evaluates the scientific foundation for the techniques used by the FBI to determine whether these techniques met appropriate standards for scientific reliability and for use in forensic validation, and whether the FBI reached appropriate scientific conclusions from its use of these techniques. This report reviews and assesses scientific evidence considered in connection with the 2001 Bacillus anthracis mailings.

Life Sciences and Related Fields: Trends Relevant to the Biological Weapons Convention - National Research Council (The National Academies Press, 2011)
During the last decade, national and international scientific organizations have become increasingly engaged in considering how to respond to the biosecurity implications of developments in the life sciences and in assessing trends in science and technology (S&T) relevant to biological and chemical weapons nonproliferation. The latest example is an international workshop, Trends in Science and Technology Relevant to the Biological Weapons Convention, held October 31 - November 3, 2010 at the Institute of Biophysics of the Chinese Academy of Sciences in Beijing. Life Sciences and Related Fields summarizes the workshop, plenary, and breakout discussion sessions held during this convention. Given the immense diversity of current research and development, the report is only able to provide an overview of the areas of science and technology the committee believes are potentially relevant to the future of the Biological and Toxic Weapons Convention (BWC), although there is an effort to identify areas that seemed particularly ripe for further exploration and analysis. The report offers findings and conclusions organized around three fundamental and frequently cited trends in S&T that affect the scope and operation of the convention: The rapid pace of change in the life sciences and related fields; The increasing diffusion of life sciences research capacity and its applications, both internationally and beyond traditional research institutions; and The extent to which additional scientific and technical disciplines beyond biology are increasingly involved in life sciences research. The report does not make recommendations about policy options to respond to the implications of the identified trends. The choice of such responses rests with the 164 States Parties to the Convention, who must take into account multiple factors beyond the project's focus on the state of the science.

Trends in Science and Technology Relevant to the Biological and Toxin Weapons Convention: Summary of an International Workshop - National Research Council (The National Academies Press, 2011)
This report offers a summary of the substantive presentations during an international workshop, Trends in Science and Technology Relevant to the Biological and Toxin Weapons Convention, held October 31 - November 3, 2010 at the Institute of Biophysics of the Chinese Academy of Sciences. It is meant to provide scientists and other technical experts with factual information about the range and variety of topics discussed at the workshop, which may be of interest to national governments and non-governmental organizations as they begin to prepare for the 7th Review Conference of the Biological and Toxin Weapons Convention (BWC) in 2011. The Beijing workshop reflected the continuing engagement by national academies international scientific organizations, and individual scientists and engineers in considering the biosecurity implications of developments in the life sciences and assessing trends in science and technology (S&T) relevant to nonproliferation. The workshop provided an opportunity for the scientific community to discuss the implications of relevant developments in S&T for multiple aspects of the BWC. Trends in Science and Technology Relevant to the Biological and Toxin Weapons Convention follows the structure of the plenary sessions at the workshop. It begins with introductory material about the BWC and current examples of the types and modes of science advice available to the BWC and other international nonproliferation and disarmament agreements, in particular the Chemical Weapons Convention (CWC). This report includes only a very brief description of the some of the post-presentation discussions held during the plenary sessions - and does not include an account of the small breakout groups - since these were intended to inform the committee's finding and conclusions and will be reflected in the final report.

Advancing Regulatory Science for Medical Countermeasure Development: Workshop Summary - Institute of Medicine (The National Academies Press, 2011)
Whether or not the United States has safe and effective medical countermeasures–such as vaccines, drugs, and diagnostic tools–available for use during a disaster can mean the difference between life and death for many Americans. The Food and Drug Administration (FDA) and the scientific community at large could benefit from improved scientific tools and analytic techniques to undertake the complex scientific evaluation and decision making needed to make essential medical countermeasures available. At the request of FDA, the Institute of Medicine (IOM) held a workshop to examine methods to improve the development, evaluation, approval, and regulation of medical countermeasures. During public health emergencies such as influenza or chemical, biological, radiological\/nuclear (CBRN) attacks, safe and effective vaccines, treatments, and other medical countermeasures are essential to protecting national security and the well being of the public. Advancing Regulatory Science for Medical Countermeasure Development examines current medical countermeasures, and investigates the future of research and development in this area. Convened on March 29-30, 2011, this workshop identified regulatory science tools and methods that are available or under development, as well as major gaps in currently available regulatory science tools. Advancing Regulatory Science for Medical Countermeasure Development is a valuable resource for federal agencies including the Food and Drug Administration (FDA), the Department of Health and Human Services (HHS), the Department of Defense (DoD), as well as health professionals, and public and private health organizations.

National Security Implications of Climate Change for U.S. Naval Forces - National Research Council (The National Academies Press, 2011)
In response to the Chief of Naval Operations (CNO), the National Research Council appointed a committee operating under the auspices of the Naval Studies Board to study the national security implications of climate change for U.S. naval forces. In conducting this study, the committee found that even the most moderate current trends in climate, if continued, will present new national security challenges for the U.S. Navy, Marine Corps, and Coast Guard. While the timing, degree, and consequences of future climate change impacts remain uncertain, many changes are already underway in regions around the world, such as in the Arctic, and call for action by U.S. naval leadership in response. The terms of reference (TOR) directed that the study be based on Intergovernmental Panel on Climate Change (IPCC) scenarios and other peer-reviewed assessment. Therefore, the committee did not address the science of climate change or challenge the scenarios on which the committee's findings and recommendations are based. National Security Implications of Climate Change for U.S. Naval Forces addresses both the near- and long-term implications for U.S. naval forces in each of the four areas of the TOR, and provides corresponding findings and recommendations. This report and its conclusions are organized around six discussion areas2014all presented within the context of a changing climate.

Opportunities in Protection Materials Science and Technology for Future Army Applications - National Research Council (The National Academies Press, 2011)
Armor plays a significant role in the protection of warriors. During the course of history, the introduction of new materials and improvements in the materials already used to construct armor has led to better protection and a reduction in the weight of the armor. But even with such advances in materials, the weight of the armor required to manage threats of ever-increasing destructive capability presents a huge challenge. Opportunities in Protection Materials Science and Technology for Future Army Applications explores the current theoretical and experimental understanding of the key issues surrounding protection materials, identifies the major challenges and technical gaps for developing the future generation of lightweight protection materials, and recommends a path forward for their development. It examines multiscale shockwave energy transfer mechanisms and experimental approaches for their characterization over short timescales, as well as multiscale modeling techniques to predict mechanisms for dissipating energy. The report also considers exemplary threats and design philosophy for the three key applications of armor systems: (1) personnel protection, including body armor and helmets, (2) vehicle armor, and (3) transparent armor. Opportunities in Protection Materials Science and Technology for Future Army Applications recommends that the Department of Defense (DoD) establish a defense initiative for protection materials by design (PMD), with associated funding lines for basic and applied research. The PMD initiative should include a combination of computational, experimental, and materials testing, characterization, and processing research conducted by government, industry, and academia.

Intelligence Analysis: Behavioral and Social Scientific Foundations - National Research Council (The National Academies Press, 2011)
The U.S. intelligence community (IC) is a complex human enterprise whose success depends on how well the people in it perform their work. Although often aided by sophisticated technologies, these people ultimately rely on their own intellect to identify, synthesize, and communicate the information on which the nation's security depends. The IC's success depends on having trained, motivated, and thoughtful people working within organizations able to understand, value, and coordinate their capabilities. Intelligence Analysis provides up-to-date scientific guidance for the intelligence community (IC) so that it might improve individual and group judgments, communication between analysts, and analytic processes. The papers in this volume provide the detailed evidentiary base for the National Research Council's report, Intelligence Analysis for Tomorrow: Advances from the Behavioral and Social Sciences. The opening chapter focuses on the structure, missions, operations, and characteristics of the IC while the following 12 papers provide in-depth reviews of key topics in three areas: analytic methods, analysts, and organizations. Informed by the IC's unique missions and constraints, each paper documents the latest advancements of the relevant science and is a stand-alone resource for the IC's leadership and workforce. The collection allows readers to focus on one area of interest (analytic methods, analysts, or organizations) or even one particular aspect of a category. As a collection, the volume provides a broad perspective of the issues involved in making difficult decisions, which is at the heart of intelligence analysis.

2009-2010 Assessment of the Army Research Laboratory - National Research Council (The National Academies Press, 2011)
The charge of the Army Research Laboratory Technical Assessment Board (ARLTAB) is to provide biannual assessments of the scientific and technical quality of the research, development, and analysis programs at the Army Research Laboratory (ARL). The advice provided in this report focuses on technical rather than programmatic considerations. The Board is assisted by six National Research Council (NRC) panels, each of which focuses on the portion of the ARL program conducted by one of ARL's six directorates. When requested to do so by ARL, the Board also examines work that cuts across the directorates. The Board has been performing assessments of ARL since 1996. The current report summarizes its finding for the 2009-2010 period, during which 96 volunteer experts in fields of science and engineering participated in the following activities: visiting ARL annually, receiving formal presentations of technical work, examining facilities, engaging in technical discussions with ARL staff, and reviewing ARL technical materials. The Board continues to be impressed by the overall quality of ARL's technical staff and their work and applauds ARL for its clear, passionate concern for the end user of its technology–the soldier in the field–and for ARL's demonstrated mindfulness of the importance of transitioning technology to support immediate and longer-term Army needs. ARL staff also continue to expand their involvement with the wider scientific and engineering community. In general, ARL is working very well within an appropriate research and development (R&D) niche and has been demonstrating significant accomplishments.

Intelligence Analysis for Tomorrow: Advances from the Behavioral and Social Sciences - National Research Council (The National Academies Press, 2011)
The intelligence community (IC) plays an essential role in the national security of the United States. Decision makers rely on IC analyses and predictions to reduce uncertainty and to provide warnings about everything from international diplomatic relations to overseas conflicts. In today's complex and rapidly changing world, it is more important than ever that analytic products be accurate and timely. Recognizing that need, the IC has been actively seeking ways to improve its performance and expand its capabilities. In 2008, the Office of the Director of National Intelligence (ODNI) asked the National Research Council (NRC) to establish a committee to synthesize and assess evidence from the behavioral and social sciences relevant to analytic methods and their potential application for the U.S. intelligence community. In Intelligence Analysis for Tomorrow: Advances from the Behavioral and Social Sciences, the NRC offers the Director of National Intelligence (DNI) recommendations to address many of the IC's challenges. Intelligence Analysis for Tomorrow asserts that one of the most important things that the IC can learn from the behavioral and social sciences is how to characterize and evaluate its analytic assumptions, methods, technologies, and management practices. Behavioral and social scientific knowledge can help the IC to understand and improve all phases of the analytic cycle: how to recruit, select, train, and motivate analysts; how to master and deploy the most suitable analytic methods; how to organize the day-to-day work of analysts, as individuals and teams; and how to communicate with its customers. The report makes five broad recommendations which offer practical ways to apply the behavioral and social sciences, which will bring the IC substantial immediate and longer-term benefits with modest costs and minimal disruption.

Examination of the U.S. Air Force's Aircraft Sustainment Needs in the Future and Its Strategy to Meet Those Needs - National Research Council (The National Academies Press, 2011)
The ability of the United States Air Force (USAF) to keep its aircraft operating at an acceptable operational tempo, in wartime and in peacetime, has been important to the Air Force since its inception. This is a much larger issue for the Air Force today, having effectively been at war for 20 years, with its aircraft becoming increasingly more expensive to operate and maintain and with military budgets certain to further decrease. The enormously complex Air Force weapon system sustainment enterprise is currently constrained on many sides by laws, policies, regulations and procedures, relationships, and organizational issues emanating from Congress, the Department of Defense (DoD), and the Air Force itself. Against the back-drop of these stark realities, the Air Force requested the National Research Council (NRC) of the National Academies, under the auspices of the Air Force Studies Board to conduct and in-depth assessment of current and future Air Force weapon system sustainment initiatives and recommended future courses of action for consideration by the Air Force. Examination of the U.S. Air Force's Aircraft Sustainment Needs in the Future and Its Strategy to Meet Those Needs addresses the following topics: Assess current sustainment investments, infrastructure, and processes for adequacy in sustaining aging legacy systems and their support equipment. Determine if any modifications in policy are required and, if so, identify them and make recommendations for changes in Air Force regulations, policies, and strategies to accomplish the sustainment goals of the Air Force. Determine if any modifications in technology efforts are required and, if so, identify them and make recommendations regarding the technology efforts that should be pursued because they could make positive impacts on the sustainment of the current and future systems and equipment of the Air Force. Determine if the Air Logistics Centers have the necessary resources (funding, manpower, skill sets, and technologies) and are equipped and organized to sustain legacy systems and equipment and the Air Force of tomorrow. Identify and make recommendations regarding incorporating sustainability into future aircraft designs.

Public Response to Alerts and Warnings on Mobile Devices: Summary of a Workshop on Current Knowledge and Research Gaps - National Research Council (The National Academies Press, 2011)
This book presents a summary of the Workshop on Public Response to Alerts and Warnings on Mobile Devices: Current Knowledge and Research Gaps, held April 13 and 14, 2010, in Washington, D.C., under the auspices of the National Research Council's Committee on Public Response to Alerts and Warnings on Mobile Devices: Current Knowledge and Research Needs. The workshop was structured to gather inputs and insights from social science researchers, technologists, emergency management professionals, and other experts knowledgeable about how the public responds to alerts and warnings, focusing specifically on how the public responds to mobile alerting.

National Earthquake Resilience: Research, Implementation, and Outreach - National Research Council (The National Academies Press, 2011)
The United States will certainly be subject to damaging earthquakes in the future. Some of these earthquakes will occur in highly populated and vulnerable areas. Coping with moderate earthquakes is not a reliable indicator of preparedness for a major earthquake in a populated area. The recent, disastrous, magnitude-9 earthquake that struck northern Japan demonstrates the threat that earthquakes pose. Moreover, the cascading nature of impacts-the earthquake causing a tsunami, cutting electrical power supplies, and stopping the pumps needed to cool nuclear reactors-demonstrates the potential complexity of an earthquake disaster. Such compound disasters can strike any earthquake-prone populated area. National Earthquake Resilience presents a roadmap for increasing our national resilience to earthquakes. The National Earthquake Hazards Reduction Program (NEHRP) is the multi-agency program mandated by Congress to undertake activities to reduce the effects of future earthquakes in the United States. The National Institute of Standards and Technology (NIST)-the lead NEHRP agency-commissioned the National Research Council (NRC) to develop a roadmap for earthquake hazard and risk reduction in the United States that would be based on the goals and objectives for achieving national earthquake resilience described in the 2008 NEHRP Strategic Plan. National Earthquake Resilience does this by assessing the activities and costs that would be required for the nation to achieve earthquake resilience in 20 years. National Earthquake Resilience interprets resilience broadly to incorporate engineering\/science (physical), social\/economic (behavioral), and institutional (governing) dimensions. Resilience encompasses both pre-disaster preparedness activities and post-disaster response. In combination, these will enhance the robustness of communities in all earthquake-vulnerable regions of our nation so that they can function adequately following damaging earthquakes. While National Earthquake Resilience is written primarily for the NEHRP, it also speaks to a broader audience of policy makers, earth scientists, and emergency managers.

Prudent Practices in the Laboratory: Handling and Management of Chemical Hazards, Updated Version - National Research Council (The National Academies Press, 2011)
Prudent Practices in the Laboratory2014the book that has served for decades as the standard for chemical laboratory safety practice2014now features updates and new topics. This revised edition has an expanded chapter on chemical management and delves into new areas, such as nanotechnology, laboratory security, and emergency planning. Developed by experts from academia and industry, with specialties in such areas as chemical sciences, pollution prevention, and laboratory safety, Prudent Practices in the Laboratory provides guidance on planning procedures for the handling, storage, and disposal of chemicals. The book offers prudent practices designed to promote safety and includes practical information on assessing hazards, managing chemicals, disposing of wastes, and more. Prudent Practices in the Laboratory will continue to serve as the leading source of chemical safety guidelines for people working with laboratory chemicals: research chemists, technicians, safety officers, educators, and students.

Tsunami Warning and Preparedness: An Assessment of the U.S. Tsunami Program and the Nation's Preparedness Efforts - National Research Council (The National Academies Press, 2011)
Many coastal areas of the United States are at risk for tsunamis. After the catastrophic 2004 tsunami in the Indian Ocean, legislation was passed to expand U.S. tsunami warning capabilities. Since then, the nation has made progress in several related areas on both the federal and state levels. At the federal level, NOAA has improved the ability to detect and forecast tsunamis by expanding the sensor network. Other federal and state activities to increase tsunami safety include: improvements to tsunami hazard and evacuation maps for many coastal communities; vulnerability assessments of some coastal populations in several states; and new efforts to increase public awareness of the hazard and how to respond. Tsunami Warning and Preparedness explores the advances made in tsunami detection and preparedness, and identifies the challenges that still remain. The book describes areas of research and development that would improve tsunami education, preparation, and detection, especially with tsunamis that arrive less than an hour after the triggering event. It asserts that seamless coordination between the two Tsunami Warning Centers and clear communications to local officials and the public could create a timely and effective response to coastal communities facing a pending tsuanami. According to Tsunami Warning and Preparedness, minimizing future losses to the nation from tsunamis requires persistent progress across the broad spectrum of efforts including: risk assessment, public education, government coordination, detection and forecasting, and warning-center operations. The book also suggests designing effective interagency exercises, using professional emergency-management standards to prepare communities, and prioritizing funding based on tsunami risk.

Building Community Disaster Resilience Through Private-Public Collaboration - National Research Council (The National Academies Press, 2011)
Natural disasters2014including hurricanes, earthquakes, volcanic eruptions, and floods2014caused more than 220,000 deaths worldwide in the first half of 2010 and wreaked havoc on homes, buildings, and the environment. To withstand and recover from natural and human-caused disasters, it is essential that citizens and communities work together to anticipate threats, limit their effects, and rapidly restore functionality after a crisis. Increasing evidence indicates that collaboration between the private and public sectors could improve the ability of a community to prepare for, respond to, and recover from disasters. Several previous National Research Council reports have identified specific examples of the private and public sectors working cooperatively to reduce the effects of a disaster by implementing building codes, retrofitting buildings, improving community education, or issuing extreme-weather warnings. State and federal governments have acknowledged the importance of collaboration between private and public organizations to develop planning for disaster preparedness and response. Despite growing ad hoc experience across the country, there is currently no comprehensive framework to guide private-public collaboration focused on disaster preparedness, response, and recovery. Building Community Disaster Resilience through Private-Public Collaboration assesses the current state of private-public sector collaboration dedicated to strengthening community resilience, identifies gaps in knowledge and practice, and recommends research that could be targeted for investment. Specifically, the book finds that local-level private-public collaboration is essential to the development of community resilience. Sustainable and effective resilience-focused private-public collaboration is dependent on several basic principles that increase communication among all sectors of the community, incorporate flexibility into collaborative networks, and encourage regular reassessment of collaborative missions, goals, and practices.

Research in the Life Sciences with Dual Use Potential: An International Faculty Development Project on Education About the Responsible Conduct of Science - National Research Council (The National Academies Press, 2011)
In many countries, colleges and universities are where the majority of innovative research is done; in all cases, they are where future scientists receive both their initial training and their initial introduction to the norms of scientific conduct regardless of their eventual career paths. Thus, institutions of higher education are particularly relevant to the tasks of education on research with dual use potential, whether for faculty, postdoctoral researchers, graduate and undergraduate students, or technical staff. Research in the Life Sciences with Dual Use Potential describes the outcomes of the planning meeting for a two-year project to develop a network of faculty who will be able to teach the challenges of research in the life sciences with dual use potential. Faculty will be able to incorporate such concepts into their teaching and research through exposure to the tenets of responsible conduct of research in active learning teaching methods. This report is intended to provide guidelines for that effort and to be applicable to any country wishing to adopt this educational model that combines principles of active learning and training with attention to norms of responsible science. The potential audiences include a broad array of current and future scientists and the policymakers who develop laws and regulations around issues of dual use.